1987
DOI: 10.4049/jimmunol.139.6.1902
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 induces interleukin 1. I. Induction of circulating interleukin 1 in rabbits in vivo and in human mononuclear cells in vitro.

Abstract: Interleukin 1 (IL-1) plays an important role in host defense mechanisms by increasing body temperature, inducing the synthesis of a variety of lymphokines and hepatic acute phase proteins and acting as a chemoattractant for lymphocytes. However, in some microenvironments such as injured tissue or joint spaces, elevated IL-1 levels may contribute to pathologic processes, for example, proliferation and fibrosis of tissue involved in pannus formation as well as degradation of matrix and abnormal tissue architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Previous literature has shown, that IL-1β can induce autocrine immune cell activation via IL1R1 thereby promoting further IL-1β secretion in a positive feedback loop in nucleated cells ( 31 ). Besides, IL-1β binding to IL1R also induces MAPK- and NFκB-activation, which can modulate immune cell activation ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature has shown, that IL-1β can induce autocrine immune cell activation via IL1R1 thereby promoting further IL-1β secretion in a positive feedback loop in nucleated cells ( 31 ). Besides, IL-1β binding to IL1R also induces MAPK- and NFκB-activation, which can modulate immune cell activation ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…31 IL-1β also works in an autoregulatory fashion to amplify its expression through a positive feedback loop that exponentially increases the inflammatory response. [32][33][34] Additionally, studies have shown that IL-1β plays a role in the induction of procoagulant activity, and the growth of vascular smooth muscle cells. 10,29 Importantly, as alluded to above, IL-1β is an upstream cytokine central to the inflammatory response that drives the IL-6 signaling pathway.…”
Section: Canakinumabmentioning
confidence: 99%
“…[1][2][3][4][5][6] TNF-α and IL-1β are produced in the early stage of in ammation and upregulate expression of themselves and other cytokines including IL-6. [7][8][9][10][11][12] IL-1β and IL-6 work synergistically to activate macrophages and B-and T-cells. [13][14][15][16][17] Ccl2 recruits monocytes and lymphocytes to in ammation sites via chemotaxis.…”
Section: Introductionmentioning
confidence: 99%